THE RELATIONSHIP BETWEEN CORAL REEFS AND COASTAL FISHERIES RESOURCES IN PANGGANG ISLAND AND SURROUNDING AREAS, SERIBU ISLANDS, JAKARTA: KETERKAITAN TERUMBU KARANG DENGAN SUMBERDAYA PERIKANAN PESISIR PULAU PANGGANG DAN SEKITARNYA, KEPULAUAN SERIBU, JAKARTA - Melindo, Hera Ledy; Kurnia, Rahmat; Yonvitner, Yonvitner (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Panggang Island has the potential for a coral reef ecosystem covering an area of around 9 ha, but the existence of coral reefs in the waters of Panggang Island and its surroundings has decreased in area. This study aims to identify the condition of coral reefs and analyze the relationship between coral reefs and reef fish biomass in the waters of Panggang Island and its surroundings. Coral reef ecosystem data collection was carried out using the Line Intercept Transect (LIT) method, while fish data collection was carried out using the underwater visual census method. The condition of the coral reefs at the research location was classified as moderate. The highest live coral cover was recorded on Panggang Island with a value of 41% and on Air Island with a value of 31%. The coral reef growth forms (life forms) at both research locations were found to be 10 types, with the highest life forms being Coral foliose and Coral encrusting. The number of coral fish observed was 867 individuals from 106 species belonging to 27 families, dominated by the family Pomacentridae (72.81%). The abundance of fish on Air Island was 386±113 individuals/250 m², and on Panggang Island it was 406±160 individuals/250 m². The highest measurement results of coral fish biomass were at Station 4 of Panggang Island (43.05 g/m²), while the lowest one was at Station 3 of Air Island (4.98 g/m²).